The effectiveness of concentrated growth factor and low level laser therapy on the healing of dry socket - Kamal, Aqsa (2021)
dry socket is a common postoperative complication following tooth extraction. It occurs due to disruption of the clot within the wound. Different methods have been advocated to treat dry socket, such as the application of turmeric, zinc oxide eugenol, Alvogyl or honey. These management strategies have been empirical for treatment of symptoms only rather than scientific. Current wound healing sciences focuses on the cellular and molecular strategies using new regenerative tools. The aim of this study is to evaluate the efficacy of concentrated growth factor (CGF) and low level laser therapy (LLLT) in the healing of dry socket following tooth extraction. The study was conducted at University Dental Hospital Sharjah, UAE. 60 patients with one dry socket each, were divided into three treatment groups based on their choice. In Group I (n=30), conventional treatment, Group II (n=15) dry sockets were treated with CGF and Group III (n=15) sockets were lased with LLLT. All dry socket patients were seen at day 0 for treatment and followed up at day 4, 7, 14 and 21. Pain score, peri-socket inflammation, peri-socket tenderness and amount of granulation tissue formation were noted. Data were analyzed as mean wound healing parameter values for each treatment group using One-way ANOVA. Statistically significant difference is kept at p<0.05. Conventional Treatment Group I took more than 7 days to match the healing phase of Group II CGF treated socket and Group III LLLT irradiated socket (p=0.001). When healing rate between CGF and LLLT are compared, LLLT Group III showed a delay of 4 days compared to CGF. CGF treated socket was superior to LLLT in its ability to generate 75% granulation tissue and eliminate pain symptom by day 7 (p=0.001).